A Review of the Impact of Internal Pay Gaps on Corporate Performance - Shen, Wenqian (Transactions on Economics, Business and Management Research, 2024)
According to tournament theory, internal pay gap is an important corporate pay incentive, and the existence of internal pay gap can improve the performance level of company. However, the social comparison theory believes that the widening of internal pay gap makes ordinary employees have unfair cognition and sense of exploitation, which is not conducive to the improvement of corporate performance. At present, there is no consensus on the empirical research conclusions of scholars. Some scholars advocate supporting the tournament theory; Some scholars support the combination of tournament theory and social comparison theory, that is, internal pay gap has an inverted U-shaped effect on performance. This paper integrates and summarizes the research on the influence of internal pay gap on corporate performance, in order to provide suggestions for corporates to formulate effective pay structure, which is conducive to the sustainable and healthy development of corporates.